Secreted glucose regulated protein78 ameliorates DSS-induced mouse colitis - Zhao, Liang; Lv, Yibing; Zhou, Xiaoqi; Guo, Zilong; Li, Heli; Guo, Yanyan; Liu, Tao; Tu, Lei; Zhu, Liangru; Tao, Juan; Shen, Guanxin; He, Yong; et al. (Frontiers in Immunology, 2023)
The secreted form of 78-kDa glucose-regulated protein (sGRP78) has been widely reported for its property in aiding resolution of inflammatory. However, little is known on its potential in the treatment of colitis. To investigate the expression pattern and functional outcome of GRP78 in ulcerative colitis, its expression was measured in human and murine colitis samples. It was found that GRP78 was spontaneously secreted to a high level in gut, which is a physiological site of immune tolerance. During the active phase of DSS-induced colitis, the sGRP78 level was significantly reduced but rebounded quickly during resolving phase, making it a potential candidate for the treatment of colitis. In the following experiments, the administration of sGRP78 was proved to decrease susceptibility to experimental colitis, as indicated by an overall improvement of intestinal symptoms, restoration of TJ integrity, decreased infiltration of immune cells and impaired production of inflammatory cytokines. And specific cleavage of endogenous sGRP78 could aggravate DSS colitis. We linked sGRP78 treatment with altered monocyte/macrophage biology and skewed macrophage polarization by inhibiting the TLR4-dependent MAP-kinases and NF-κB pathways. Based on these studies, as a naturally occurring immunomodulatory molecule, sGRP78 might be an attractive novel therapeutic agent for acute intestinal inflammation.